Economic valuation of whale shark tourism in Cenderawasih Bay National Park, Papua, Indonesia - ZUZY ANNA; DICKY SURYA SAPUTRA (Society for Indonesian Biodiversity, 2017)
Anna Z, Saputra DS. 2017. Economic valuation of whale shark tourism in Cenderawasih Bay National Park, Papua, Indonesia. Biodiversitas 18: 1026-1034. The whale sharks aggregation in the waters of Cenderawasih Bay has an impact on improving the marine tourism industry in the region. On the other hands, Whale Shark is one of the species listed in the Red List of Threatened Species by the International Union for Conservation of Nature (IUCN), the vulnerable status, means that a whale shark populations have been reduced by 20% to 50% within 10 years or three generations. The decline numbers of whale sharks caused by human activities that damage the fish and the habitat, such as fishing and tourism activities. This is due to the lack of public awareness about the function and value of these resources and its habitat. The whale shark has inherent value as marine resources, and has an environmental services value, in relation to tourism activities. This paper measures the economic value and environmental services of the whale shark and its habitat. The method of Travel Cost is used to calculate the value of expenditures incurred by both foreign and local tourists. The study also measured the value obtained by tourist operators, the value of fishing activities, and the value of the habitat, through the people's Willingness to Pay (WTP), using Contingent Valuation Method (CVM). From the result of the overall economic valuation can be determined the estimated value of whale shark tourism, as well as Cenderawasih Bay National Park area, amounted to IDR 35.5 trillion. The policy implication of this research is the need for appreciation of the whale sharks value, as well as its habitat, by managing and developing conservation areas, and community capacity building on the understanding of the importance of whale sharks and its conservation.